Concrete Constraint Guided Symbolic Execution - Sun, Yue; Yang, Guowei; Lv, Shichao; Li, Zhi; Sun, Limin (Proceedings / International Conference on Software Engineering, 2024)
Symbolic execution is a popular program analysis technique. It systematically explores all feasible paths of a program but its scalability is largely limited by the path explosion problem, which causes the number of paths proliferates at runtime. A key idea in existing methods to mitigate this problem is to guide the selection of states for path exploration, which primarily relies on the features to represent program states. In this paper, we propose concrete constraint guided symbolic execution, which aims to cover more concrete branches and ultimately improve the overall code coverage during symbolic execution. Our key insight is based on the fact that symbolic execution strives to cover all symbolic branches while concrete branches are neglected, and directing symbolic execution toward uncovered concrete branches has a great potential to improve the overall code coverage. The experimental results demonstrate that our approach can improve the ability of KLEE to both increase code coverage and find more security violations on 10 open-source C programs.